Engineering geological investigations of the Trishuli-Galchhi Hydroelectric Project - K.C., Jyoti Kumar (Bulletin of the Department of Geology, 2010)
DOI: 10.3126/bdg.v13i0.3963 Bulletin of the Department of Geology Vol.13 2010, pp.23-36